Trade tales : decoding customers' stories - Woodside, Arch G. (Advances in culture, tourism and hospitality research, 2018)
To clarify their own thinking, gain confirmation, and plan, customers tell stories about their interactions with sales and service associates. These stories are told often via blog sites, social-media platforms (e.g. TripAdvisor) as well as informally to friends and family members. Read original first-person stories of problems, opportunities and outcomes with a multiple-choice exercise following each story, as well as a critical review by an independent researcher. This volume describes customers' reports of their experience of interactions with sales/service associates. Chapters also offer a descriptive theory of storytelling narratives of these encounters. Gain an international view with stories by Asian, European, New Zealand/Pacific Rim, and North American customers. The volume highlights small details that have significant impact on customer satisfaction enhancing the reader's abilities to detect nuances in multiple international contexts, understand how customers evaluate sales/service reps' behavior well as providing opportunities to solve real problems. This is a valuable book in the field of customer relationship management that is also interactive.